2017
DOI: 10.1186/s12933-017-0542-6
|View full text |Cite
|
Sign up to set email alerts
|

Target organ damage and incident type 2 diabetes mellitus: the Strong Heart Study

Abstract: BackgroundRecent analyses in a registry of hypertensive patients suggested that preceding left ventricular (LV) hypertrophy (LVH) and/or carotid atherosclerosis are associated with incident type 2 diabetes, independent of confounders. We assess the relation between prevalent cardio-renal target organ damage (TOD) and subsequent incident type 2 diabetes in a population-based study with high prevalence of obesity.MethodsWe selected 2887 non-diabetic participants from two cohorts of the Strong Heart Study (SHS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 41 publications
1
33
0
1
Order By: Relevance
“…28 The thin-walled structure makes LA particularly vulnerable to volume and pressure-load conditions from long-standing elevated LV filling pressure, resulting in chamber dilation or geometric alterations with greater susceptibility for AF. 33 In fact, the Cardiovascular Health Study reported that LA may actually remodel more severely from anteroposterior direction with HF. 19 Owing to the complex geometry, it has been proposed that LAD may not enlarge equally as atrial remodelling progresses, which makes precise quantification of LA size clinically challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 The thin-walled structure makes LA particularly vulnerable to volume and pressure-load conditions from long-standing elevated LV filling pressure, resulting in chamber dilation or geometric alterations with greater susceptibility for AF. 33 In fact, the Cardiovascular Health Study reported that LA may actually remodel more severely from anteroposterior direction with HF. 19 Owing to the complex geometry, it has been proposed that LAD may not enlarge equally as atrial remodelling progresses, which makes precise quantification of LA size clinically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…18 Our data showed a significant difference between guideline-defined 'normal' and 'DD' groups (30.9 vs. 36.5 mm for all participants, P < 0.001) in both sexes, which challenges the traditional concept that LAD may be neither sensitive enough nor clinically feasible for assessment of LA remodelling in daily practice. 33,35 This may be partly explained by the fact that LAD assessment is a relatively robust, simple measure with potentially higher reproducibility. Our data also suggested the potential use of LAD (34 mm) as useful threshold in identifying DD with relatively high accuracy (AUROC: 77%; sensitivity/specificity: 74/68.8%; and NPV: >95%) and relatively high specificity (86.7%) in identifying LA enlargement (>34 mL/m 2 ; LAD: 37 mm) with good PPV (Table 3), indicating the potential feasibility in 'labelling' Stage B HF and help establish the clinical diagnosis of HFpEF recommended by most updated ESC HF guideline criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemia (Gateva et al, 2017), and diabetes (de Simone et al, 2017) are also highly associated with obesity. However, it is currently unknown whether the molecular changes of cardiac ion channels in diabetic patients without obesity recapitulate that in obesity.…”
Section: Delayed Rectifier K Currents (Ikur Ikr and Iks) And Obesitymentioning
confidence: 99%
“…Visceral adipose tissue synthesizes and secretes a huge amount of hormonally active substances that determines the development of eating disorders, IR and impaired glucose metabolism with the development of diabetes, AH and LV hypertrophy, dyslipidemia, microalbuminuria, hypercoagulation syndrome [4].…”
Section: Introductionmentioning
confidence: 99%